English Language Teaching and Learning Issues in Malaysia: Learners' Perceptions via Facebook Dialogue Journal - Wendy Hiew (researchers world, 2012)
The purpose of this research was to gather English as a second language (ESL) learners perceptions pertaining to their experience in learning English language in secondary schools, colleges and local universities. The research methodology incorporated dialogue journal using Facebook. Dialogue journal is a written communication between a teacher and students or other writing partners, which provides a natural context for language development and a new channel of communication outside the classroom. The research incorporated Facebook as it is currently one of the most prominent online social networking sites among Malaysians. 46 respondents from public and private colleges and universities discussed various learning issues including impediments that they encountered during English lessons in secondary school, college and university; learners’ views and comments on the issues pertaining to local English language teaching and learning; and suggestions to improve the teaching and learning of English. The discussion revealed varying viewpoints such as difficulties and reasons that students faced in learning the four language skills i.e. speaking, listening, reading and writing; and the lack of confidence which hampered their language improvement. This research hopes to enlighten educators of arduous challenges that students faced in learning the English language so that they may strive to improve and consolidate their teaching skills, thus, making language teaching and learning more effective and meaningful for both teachers and students.